Importance of tyrosine phosphorylation in receptor kinase complexes. (May 2015) - Macho, Alberto P.; Lozano-Durán, Rosa; Zipfel, Cyril
Highlights: Components of brassinosteroid and PAMP receptor complexes are phosphorylated on tyrosine residues. Tyrosine phosphorylation is an important mechanism for the activation of receptor kinase complexes. Phosphorylation of specific tyrosine residues could contribute to specific signaling outcomes. Abstract : Tyrosine phosphorylation is an important post-translational modification that is known to regulate receptor kinase (RK)-mediated signaling in animals. Plant RKs are annotated as serine/threonine kinases, but recent work has revealed that tyrosine phosphorylation is also crucial for the activation of RK-mediated signaling in plants. These initial observations have paved the way for subsequent detailed studies on the mechanism of activation of plant RKs and the biological relevance of tyrosine phosphorylation for plant growth and immunity. In this Opinion article we review recent reports on the contribution of RK tyrosine phosphorylation in plant growth and immunity; we propose that tyrosine phosphorylation plays a major regulatory role in the initiation and transduction of RK-mediated signaling in plants.